Calmangafodipir Reduces Sensory Alterations and Prevents Intraepidermal Nerve Fibers Loss in a Mouse Model of Oxaliplatin Induced Peripheral Neurotoxicity - Canta, Annalisa (Antioxidants (Basel), 2020)
Oxaliplatin (OHP) is an antineoplastic compound able to induce peripheral neurotoxicity. Oxidative stress has been suggested to be a key factor in the development of OHP-related peripheral neurotoxicity. Mangafodipir, a contrast agent possessing mitochondrial superoxide dismutase (MnSOD)-mimetic activity, has been tested as a cytoprotector in chemotherapy-induced peripheral neurotoxicity (CIPN). Calmangafodipir (PledOx(®)) has even better therapeutic activity. We investigated a BALB/c mouse model of OHP-related CIPN and the effects of the pre-treatment of calmangafodipir (2.5, 5, or 10 mg/kg intravenously) on sensory perception, and we performed a pathological study on skin biopsies to assess intraepidermal nerve fiber (IENF) density. At the end of the treatments, OHP alone or in pre-treatment with calmangafodipir 2.5 and 10 mg/kg, induced mechanical allodynia and cold thermal hyperalgesia, but calmangafodipir 5 mg/kg prevented these effects. Accordingly, OHP alone or in pre-treatment with calmangafodipir 2.5 and 10 mg/kg, induced a significant reduction in IENF density, but calmangafodipir 5 mg/kg prevented this reduction. These results confirm a protective effect of calmangafodipir against OHP-induced small fiber neuropathy. Interestingly, these results are in agreement with previous observations suggesting a U-shaped effect of calmangafodipir, with the 10 mg/kg dose less effective than the lower doses.